Post‐COVID‐19 splenic infarction in a patient with chronic atrial fibrillation: A case report - Roham Sarmadian; Reza Ghasemikhah; Hossein Sarmadian; Mahmood Khosravi; Saeed Hassani (Clinical Case Reports, 2022)
Abstract We describe splenic infarction (SI), an infrequent condition, in an 82‐year‐old COVID‐19 patient with chronic atrial fibrillation (AF). COVID‐19 may cause thrombosis, and AF is a predisposing factor for splenic infarction. Suspicion of SI may be warranted in COVID‐19 patients with abdominal pain, especially if a predisposing factor exists.